Financial Performance Analysis Using Du Pont at PT. Wijaya Karya TBK Period 2019-2023 - PARDEDE, Mazmur (International Journal of Environmental, Sustainability, and Social Science, 2024)
This research aims to analyze the performance of PT Wijaya Karya Tbk in 2019–2023 using the Du Pont analysis tool by looking at NPM, ROA, ROE, EM, and TATO. From the results of this research, it can be seen that the maximum NPM was in 2019, which was 9.6%, which means that PT Wijaya Karya Tbk's ability to generate profit compared to sales was 9.6%. While the lowest was in 2023 where the company was unable to generate net profit or experienced losses. The highest TATO in 2019 was 43.8%, which means that PT Wijaya Karya Tbk ability to generate profit using assets was 43.8%. And the minimum TATO was in 2020, which was 24.3%. The highest EM in 2023 was 689.3%, which means that the ratio of total assets to equity was 689.3%. The minimum EM occurred in 2019, which was 323.2%. The highest Du Pont ROE was in 2019, which was 13.64% and the lowest was -81.7% in 2023.